2023
DOI: 10.3390/cancers15041086
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Medulloblastoma Is Driven by YB-1, ABCB1 and a Seven-Gene Drug Signature

Abstract: Therapy resistance represents an unmet challenge in the treatment of medulloblastoma. Accordingly, the identification of targets that mark drug-resistant cell populations, or drive the proliferation of resistant cells, may improve treatment strategies. To address this, we undertook a targeted approach focused on the multi-functional transcription factor YB-1. Genetic knockdown of YB-1 in Group 3 medulloblastoma cell lines diminished cell invasion in 3D in vitro assays and increased sensitivity to standard-of-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The over-expression of this protein has been also reported in a number of cancers, including renal cell carcinoma [87], and breast cancer [88]. One of the main conclusions of the investigation by Taylor et al [85] is the association between YB-1 expression and various aspects of medulloblastoma tumorigenesis, including cell invasion, MYC oncoprotein activity and lipid metabolism. The same study also found an evident correlation between high expression of the YB-1 gene and poor survival outcomes of patients in three out of four subgroups of medulloblastoma.…”
Section: Drug Resistance In Childhood Cancersmentioning
confidence: 94%
See 1 more Smart Citation
“…The over-expression of this protein has been also reported in a number of cancers, including renal cell carcinoma [87], and breast cancer [88]. One of the main conclusions of the investigation by Taylor et al [85] is the association between YB-1 expression and various aspects of medulloblastoma tumorigenesis, including cell invasion, MYC oncoprotein activity and lipid metabolism. The same study also found an evident correlation between high expression of the YB-1 gene and poor survival outcomes of patients in three out of four subgroups of medulloblastoma.…”
Section: Drug Resistance In Childhood Cancersmentioning
confidence: 94%
“…This form of cancer comprises four principal molecular groups with different patterns of metastasis and overall prognosis. The association of higher expression of MDR proteins with chemoresistance was reported almost 30 years ago [85]. The authors reported increased MDR1 expression that correlated with poor outcomes of medulloblastoma (MB).…”
Section: Drug Resistance In Childhood Cancersmentioning
confidence: 99%
“…Three vehicle and cis-tolerant MB Group3 cell lines (DT-D283-DMF, DT-D283-Cis, DT-HD-MB03-DMF, DT-HD-MB03-Cis, DT-D458-DMF and DT-D458-Cis) were utilised, as previously published. 21 The DT-D283 and DT-D458 lines were derived in-house whereas the DT-HD-MB03-Cis was obtained from Gianpiero Di Leva (Keele University, UK). DT-D283 and DT-D458 cells were cultured in DMEM with 10% fetal bovine serum and the DT-D283-Cis DT and DT-D458-Cis DT supplemented with 1.6 and 0.6 µM cis (Selleckchem (Houston, TX, USA), S1166) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Akin to the DT-DAOY cells, cis-resistant cell lines DT-D458, DT-HD-MB03 and DT-D283 were also generated in a similar manner. 21 In brief, cells were treated with increasing doses of cis until their EC 50 exceeded the treatment dose or was significantly increased in comparison to the vehicle cell line (DMF).…”
Section: Methodsmentioning
confidence: 99%
“…It becomes clear that a better understanding of the molecular downstream effects of HDAC inhibition, as well as the development of predictive biomarkers for patient selection is crucial to translate promising preclinical findings [ 16 ]. Additionally, it is important to consider that aggressive cancers such as MYC -amplified Group 3 MB have a strong capacity to develop therapy evasion mechanisms and resistance when confronted with highly cytotoxic multimodal chemotherapy [ 17 ]. In line with this observation, single agent targeted treatment approaches are not likely to induce long term responses in high-grade solid tumors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%